Health behaviors and mental health during the COVID-19 pandemic: A longitudinal population-based survey in Germany. (October 2021) - Mata, Jutta; Wenz, Alexander; Rettig, Tobias; Reifenscheid, Maximiliane; Möhring, Katja; Krieger, Ulrich; Friedel, Sabine; Fikel, Marina; Cornesse, Carina; Blom, Annelies G.; Naumann, Elias
Abstract: Objective: To understand the mental health response to repeated and prolonged stress during the COVID-19 related lockdown and the role of specific health behaviors to buffer against this stress. Methods: In a longitudinal study with several measurement points covering three months during the COVID-19 pandemic, about 3500 randomly selected participants representative of the German population reported on their mental health (anxiety, depression, loneliness) and health behaviors (screen time, snack consumption, physical activity). Results: Symptoms of anxiety, depression, and loneliness were highest shortly after the lockdown came into effect. Over time, the symptoms were stable or went down slightly, corresponding to patterns of habituation. Among people with higher vulnerability to poor mental health during the lockdown (e.g., women), the proportion with high levels of anxiety, depression, and loneliness was considerably larger. These groups also reported fewer health-promoting behaviors. More screen time, more snacking, and less physical activity were related to higher symptoms of anxiety, depression, and loneliness across all time points. Changes in health behaviors over time mostly did not predict changes in mental health symptoms. Conclusions: Mental health and engagement in protective health behaviors was lowest at the start of the lockdown. Health behaviors mostly returned to pre-lockdown levels within three months. Engaging in healthier behaviors was associated with better mental health. Policy implications of these findings are discussed. This study provides important insights into (unintended) side effects of an international crisis and can contribute to a better understanding of how to preserve mental health. Highlights: Anxiety, depression, and loneliness symptoms were highest at start of lockdown. More screen time, more snacking, less physical activity related to less mental health. Overall participants reported good mental health during first months of lockdown. People vulnerabe to poor mental health showed more anxiety, depression, loneliness. People with vulnerabilities also reported fewer health-promoting behaviors.